Renin‐angiotensin system and fibrosis in non‐alcoholic fatty liver disease. (5th July 2014) - Goh, George B; Pagadala, Mangesh R; Dasarathy, Jaividhya; Unalp‐Arida, Aynur; Sargent, Ruth; Hawkins, Carol; Sourianarayanane, Achuthan; Khiyami, Amer; Yerian, Lisa; Pai, Rish; McCullough, Arthur J; Dasarathy, Srinivasan
Abstract Background & Aims Therapeutic options are limited for patients with non‐alcoholic fatty liver disease (NAFLD). One promising approach is the attenuation of necroinflammation and fibrosis by inhibition of the renin‐angiotensin system (RAS). We explored whether the risk of fibrosis was associated with the use of commonly used medications in NAFLD patients with hypertension. Specifically, we sought to determine the association between RAS blocking agents and severity of hepatic fibrosis in NAFLD patients with hypertension. Methods Cross‐sectional study where clinical information including demographics, anthropometry, medical history, concomitant medication use, biochemical and histological features were ascertained in 290 hypertensive patients with biopsy proven NAFLD followed at two hepatology outpatient clinics. Stage of hepatic fibrosis was compared in patients with and without RAS blocker use. Other risk factors for fibrosis were evaluated from the electronic medical records and patient follow‐up. Results Baseline characteristics of hypertensive patients treated with and without RAS blockers were similar except for less ballooning (1.02 vs. 1.31, P = 0.001) and lower fibrosis stage (1.63 vs. 2.16, P = 0.002) in patients on RAS blockers On multivariate analysis, advancing age (OR: 1.04; 95%CI: 1.01–1.06, P = 0.012) and presence of diabetes (OR: 2.55; 95%CI: 1.28–5.09, P = 0.008) had an independent positive association, while use of RAS blockers (OR: 0.37; 95%CI: 0.21–0.65, P = 0.001) and statins (OR: 0.52; 95%CI: 0.29–0.93, P = 0.029) had a negative association with advanced fibrosis. Conclusion Hypertensive patients with NAFLD on baseline RAS blockers had less advanced hepatic fibrosis suggesting a beneficial effect of RAS blockers in NAFLD.